UNPACKING THE PLACE OF ARCHAEOLOGY AND HERITAGE IN PANDEMIC STUDIES - NOMISHAN, Terngu Sylvanus (Journal of Social Sciences)
Archaeology offers a 3.5 million-year-long scientific record of human and earlier hominine problem-solving and thus has the potential to research very deep into the past human solutions to pandemics and epidemics. Heritage on the other hand acts as a positive enabler for the complex, multi-vector challenges of today’s world, such as cultural and environmental sustainability, economic inequalities, conflict resolution, social cohesion and the future of cities among others. In this way, the remote past has the capacity to educate the present world on how to cope with pandemic diseases and similar challenges in the contemporary era. Therefore, this essay seeks to open a discourse on the ways in which archaeology and heritage can contribute to the prevention and control of the present COVID-19 pandemic and similar others in the present and future. Therefore, the government and other agencies funding research pertaining to the discovery of the ways through which pandemics can be treated, controlled and prevented, need also to explore the option of archaeology and heritage studies, so as to trace the root causes of pandemic diseases. This will lead to the discovery of traditional means of treating, controlling and preventing pandemic outbreaks. This underscores the argument that almost everything that exists in the present day has some historical antecedence.